2018
DOI: 10.1007/s13193-018-0777-z
|View full text |Cite
|
Sign up to set email alerts
|

Carcinosarcoma of Breast Mimicking Breast Abscess

Abstract: Carcinosarcoma, a tumor having both carcinomatous and sarcomatous elements, occurring in the breast, is a rare condition. The tumor consists of both epithelial and mesenchymal cell lines and tends to behave aggressively. It has clinical features like that of invasive breast carcinoma but sometimes there can be diagnostic confusion as it can mimic or present as breast abscess. Treatment is multimodal. Surgery plays the vital role. Post-op radiation and chemo are indicated. Hormone therapy is usually inapplicabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…The clinical symptoms of breast carcinosarcoma are similar to invasive ductal carcinoma, and include the presence of a large painful mass, nipple discharge, nipple depression, and skin ulceration (7,8,12,14). One study reported a case of carcinosarcoma presenting as a breast abscess (15). In the present case, the affected mammary gland showed the signs of local inflammation, including redness and swelling of the skin overlying the mass.…”
mentioning
confidence: 57%
“…The clinical symptoms of breast carcinosarcoma are similar to invasive ductal carcinoma, and include the presence of a large painful mass, nipple discharge, nipple depression, and skin ulceration (7,8,12,14). One study reported a case of carcinosarcoma presenting as a breast abscess (15). In the present case, the affected mammary gland showed the signs of local inflammation, including redness and swelling of the skin overlying the mass.…”
mentioning
confidence: 57%
“…Due to the specific histologic feature, breast carcinosarcoma may have different biological characteristics when compared with IDC. Because of the rarity of breast carcinosarcoma, previous publications about this disease were a few small sample size retrospective analyses [ [8] , [9] , [10] , [11] , [12] , [13] , [14] ] and a few case reports [ [15] , [16] , [17] , [18] , [19] , [20] ]. From these limited studies, it appears that breast carcinosarcoma is always aggressive, poorly differentiated, and hormone receptor-negative [ 8 , 10 ].…”
Section: Introductionmentioning
confidence: 99%